DESIGN AND IMPLEMENTATION OF GRAPHICAL MULTIPLAYER GAME ON BREW SIMULATOR - NASUTION (NIM 13202122), ZULKIPLI
Game industry is one of the major industries in the world at this time. Even in the midst of the economic crisis of the world, the industry is still experiencing growth. Indutri game has even long into the game indutri handset. In abroad countries, CDMA handset game has multiplayer scheme, but until now CDMA handsets multiplayer games has not been introduced in Indonesia. Potential multiplayer games of CDMA handset in Indonesia have not been implemented. This study aims to design and implement multiplayer game design into an application. Application development game requires a systematic process. The first stage is the concept of making games that will be created. The second phase is a programming game. Third stage is the programming server. The last phase is connecting between the application with the server. Results from this research is a graphical multiplayer Tebak Kata game.